The Implied Cultural Coordinations in the Poem of Um Al-Marathi for Ibn Nuwaira Al-Yarbui - Dr.Ezzulddin Sekhi Khudhair (Journal of College of Education, 2024)
The present research aims at the discovery of the hidden cultural modes in the poem of Um Al- Marathi by Maithem Bi Noaira Al- Yarboei. It is a poem which is related to the event of his brother killing whose name Maalik, simply because he did not follow the procedure of paying Al- Zakaat. The form of the peom’s writing was achieved by the heritage of Al-Jahilia mode of literary writing. which is basically based on the principles of ethics, courage and all the means of help and support …., etc. which were annexed as a process of completion, and being associated with his brother whose name is Maalik.The hidden mode of the poem corresponds its apparent mode in the notion that the death of maalik is associated with the death of his brother maalik.  The poet uses the mode of Al- Jahilia instead of Islamic writing; unconsciously as a reaction against authority which is from his point of view which did not take an action towards his brohter’s killing. The verdict that is faced by the killer was to pay blood money. Therefore, the hidden meaning of the poem refer to his criticism against the authority.
Keywords: cultural critiris, culture, coordination, implied coordination, ibn-nuwaira